A Review of FPGA-based Implementation related to Electrical Engineering and Contribution to MPPT, Converter and Motor Drive Control - Sidek, Azmi; Md Som, Mohamad (Multidisciplinary Applied Research and Innovation, 2020)
This review is focused on the contribution of FPGA in Electrical Engineering as a system control platform and measurement instruments in three major application i.e. maximum power point tracking (MPPT), converters and motor control system. As system efficiency remain the main focus of photovoltaic (PV) system, interconnected system with various configuration requires rapid processing and more complex control algorithm. As MPPT target the overall system, converters within PV system and hybrid motor control also need a processing platform that is more flexible thus meet the ever-changing demand of the system.  Providing much flexible platform that support complex algorithm with more resources is the main attraction of using FPGA platform to develop Electrical Engineering system control application. Implementation of FPGA based system control mainly for optimizing control algorithm for pattern switching, artificial intelligent hybrid system and continuous on-line real time monitoring. In contrast with other digital platform such as microcontroller and application-specific integrated circuit, FPGA remain dominant in computational execution time, higher throughput and flexibility.